Role of Natural Protein Adequate Intake in Enhancing Anaerobic Power of Bodybuilders following 8-Week Resistance Training Program - Syed Muhammad Bilal Gillani; Soniha Aslam (The Sky, 2023)
This study aimed to investigate the effects of natural daily adequate protein intake on the anaerobic power of bodybuilders undergoing 8-week resistance training program. Thirty-one participants were randomly assigned to a group (n=31) who consumed their daily protein requirements from their regular diet. Participants' age, height, weight, and Body Mass Index were measured before and after the program. The anaerobic power of all participants was assessed pre- and post-8-week resistance training program through tests including 1 RM (Bench Press), 1 RM (Squats), 30-meter sprint test, Vertical Jump Test, and Peak Power Test (wingate test). The results showed a significant improvement in the anaerobic power of participants after the 8-week program. These findings suggest that natural daily adequate protein intake from regular diet can lead to significant improvements in anaerobic power of bodybuilders undergoing 8-week resistance training program. Therefore, coaches and athletes can focus on a balanced, nutrient-dense diet to meet their protein needs and enhance their anaerobic power without relying solely on protein supplements.